Mutation analysis of the ATP2C1 gene in Taiwanese patients with Hailey-Hailey disease - Meng-Chi Wu; Yi-Chen Liao; Sheau-Chiou Chao (Wolters Kluwer Medknow Publications, 2010)
Background: Hailey-Hailey disease (HHD) is an autosomal dominant disorder with recurrent pruritic vesicles and erosions, and scaly erythematous plaques, particularly involving intertriginous areas such as the neck, axillae, groins and perineum. Histopathology shows intraepidermal vesiculation with acantholysis in the suprabasal layer. It is caused by heterozygous mutations in the ATP2C1 gene, which encodes for the human secretory pathway Ca2+/Mn2+ ATPase 1. In this study, we analyze the mutations of the ATP2C1 gene in 26 Taiwanese patients with HHD. Methods: In total, 21 familial cases from seven families and 5 sporadic cases (including 7 previously reported) were retrieved from the medical records. The diagnosis of HHD was made based on the characteristic clinical features and histopathological evidence. All 27 exons and flanking intron boundaries were amplified by polymerase chain reaction and the products were analyzed by direct sequencing. Results: We identified three nonsense mutations (R39X, R468X, R783X), two splice-site mutations (483 + 2t→a, 832G→A), four deletion mutations (nt884-904del, 1459delCTCA, 1874delA, 1975delA) and one missense mutation (A730T). Two unrelated families with nonsense mutation R783X had the comorbidity of chronic schizophrenia since the third decade. Conclusions: We report two novel mutations (832G→A and 1874delA) of ATP2C1 involved in HHD. The nonsense mutation R783X might represent a mutational "hotspot" in the ATP2C1 gene. The present study demonstrates that a spectrum of ATP2C1 gene mutations is present in Taiwanese HHD patients.